NAVIGATING REGIONAL SECURITY: UNRAVELING DYNAMICS AMIDST THE ISRAEL-PALESTINE CONFLICT - Dr. Muhammad Tahir Rashid; Dr. Syed Muhammad Raza Zaidi; Minal Mustaqeem (International Journal of Contemporary Issues in Social Sciences, 2024)
The study aims to analyze the intricate regional security dynamics stemming from the Israel-Palestine conflict. Grounded in a thorough review of existing literature, the research employs a multidisciplinary approach, integrating political, historical, and security studies. Results highlight the multifaceted nature of regional security challenges and their interconnectedness with the protracted conflict. The findings underscore the need for nuanced policy interventions that consider historical context and regional intricacies. Recommendations emphasize the importance of diplomatic initiatives, conflict resolution frameworks, and regional cooperation to foster lasting stability. Overall, this research contributes valuable insights to the understanding of complex regional security landscapes influenced by the Israel-Palestine conflict, offering a foundation for informed decision-making and policy formulation.